Accuracy and reliability of Tzanck test compared to histopathology for diagnosis of basal cell carcinoma - Vivek Kumar Dey; Manasi Thawani; Neha Dubey (Wolters Kluwer Medknow Publications, 2015)
Background: Histopathology is considered the gold standard for diagnosis of basal cell carcinoma (BCC) but is time consuming and needs expertise to make a correct diagnosis. On the other hand, Tzanck test is a simple, easy, inexpensive and rapid test which uses exfoliative cytology to make a diagnosis. Objective: To compare the results of Tzanck test with histopathology in the diagnosis of BCC and to evaluate the diagnostic reliability and accuracy of Tzanck test in BCC. Materials and Method: Twenty-six patients with clinical suspicion of BCC were recruited. Samples for Tzanck test and histopathology were taken and diagnoses made independently. Results of Tzanck test were compared with histopathology. Results: Twenty-three cases were histopathologically proved to be BCC. Tzanck test correlated in 12 cases of BCC and could exclude all three non-BCC lesions. In 11 cases it failed to diagnose BCC. The sensitivity and specificity of Tzanck test were 52.2% and 100%, respectively, and positive and negative predictive values were 100% and 21.4%. Conclusion: Tzanck test can be recommended for initial, rapid evaluation of a clinically diagnosed case of BCC. Under experienced hands, it reliably confirms BCC. The limitation is low negative predictive value. Since it does not give information about subtypes of BCC which is of great value in therapeutic planning, histopathological confirmation is mandatory.